1996
DOI: 10.1002/(sici)1097-4628(19960314)59:11<1709::aid-app6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of EB-crosslinking on barrier properties of HDPE-mica composites

Abstract: SYNOPSISHigh-density polyethylene (HDPE) was compounded with untreated and surface-treated mica (10,20,40 wt %) and composites were injection-molded. The composites were radiation crosslinked (100, 300, 700 kGy) and hydrocarbon permeability, tensile impact strength, and tensile strength at 25 and 80°C of the composites were examined. The permeability of HDPE decreased from 7 to 3.6 g/(d X m2) by compounding the polymer with 20 wt % mica, and the permeability was additionally reduced to 1.3 g/(d X m2) by irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Similarly, the nanocomposites with a grafted matrix yielded better barrierity after crosslinking. This effect was explained by a reduction in the chain mobility of the polymer as a result of crosslinking in the amorphous regions and was reported by Sodergard et al55…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Similarly, the nanocomposites with a grafted matrix yielded better barrierity after crosslinking. This effect was explained by a reduction in the chain mobility of the polymer as a result of crosslinking in the amorphous regions and was reported by Sodergard et al55…”
Section: Resultssupporting
confidence: 52%
“…Then, effects of clay intercalation and silane grafting on the thermal and rheological properties and oxygen permeability of the nanocomposites was elucidated. We also explain the results about effects of post crosslinking of the prepared nanocomposites (due to the moisture curing of grafted PE) for further enhancement of the barrierity54, 55 and other properties as well as stabilization of the microstructure.…”
Section: Introductionmentioning
confidence: 85%
“…The gel corresponds with the network structure in an amorphous region of nylon 66 due to the insolubility of the material. A previous study reported that Efs-crosslinking increased gel content [10,13,14]. Sengupta et al [10] also reported that, below 200 kGy, there is an absence of any gel content.…”
Section: Gel Content and Degree Of Swellingmentioning
confidence: 91%
“…[1][2][3][4] . The common problems in filler-reinforced polymer composites is the poor interfacial interaction between polymer and fillers.…”
Section: Introductionmentioning
confidence: 99%